An evaluation of the English for specific purposes curriculum in a Malaysian polytechnic / Harlini Khairuddin - Khairuddin, Harlini (2011)
The English for Specific Purposes (ESP) curriculum in the General Studies component of Malaysian polytechnics holds the objective of equipping the learners with necessary workplace English language skills as well as technical contexts in order to enable them to perform in the workplace. It plays a vital role to ensure the polytechnic graduates are able to compete in the job market with adequate proficiency in English language. Henceforth, this study sets out to evaluate the current English for Specific Purposes (ESP) curriculum in Politeknik Kota Bharu, Kelantan. The purpose of this study was to investigate to what extent the ESP curriculum is adequate and relevant in preparing the students for their workplace by looking into its’ syllabus, module as well as the feedback from the students and English language lecturers. The study adopted a mixed method research design whereby a quantitative survey method was complimented by qualitative interviews and document analyses in obtaining all the data from samples and relevant information. The data from the questionnaires were analyzed using SPSS version 17 to produce descriptive statistics. Data from the interviews were analyzed according to theme and categories. A total of 90 final semester students of Diploma in Mechanical Engineering (Automotive) and 5 English language lecturers from Politeknik Kota Bharu were involved in this study. The findings disclosed that 84 .4% of the students agreed that the ESP A5003 English for Technical Purposes course is relevant. As for the English language lecturers, although they felt the course’s content seems to be insufficient in certain aspects, nonetheless they believed some of the course’s content was still relevant in preparing the students for the work place. Next, in deciding the adequacy of the ESP A5003 English for Technical Purposes course, majority of the students (82.2%) were satisfied with the adequacy of the content and felt that the course was sufficient to train them for their future work place. All the English language lecturers involved had felt the same about the course. Results also revealed that the students considered all the English language skills in the ESP A5003 English for Technical Purposes course were important for their future work place with speaking skills indicated the most important (mean=3.767, s.d=1.08l5), followed by listening skills (mean=3.733, s.d=1.0579), reading skills (mean=3.667, s.d=.9481), and writing skill (mean=3.622, s.d=1.0120). As for the English language lecturers, they agreed that all the four skills were equally important for the students. Majority of the students felt that the topics in the ESP A5003 English for Technical Purposes module were very useful in preparing them for the future work place although all the lecturers believed that the content and presentation of the topics were totally out dated and it was critically in need to be reviewed. Several recommendations related to the ESP curriculum were promoting autonomous learning to the students, changing the roles of the lecturers as facilitators, English language lecturers be given proper courses on how to teach and design ESP materials, adding more contact hours to the ESP course to include more communicative activities and to produce an additional manual that offer the background knowledge, terminologies and useful phrases of the related disciplines for use by the students and the English language lecturers. It is recommended that similar study be carried out to involve all polytechnics in Malaysia and also involving students of other programmes as well.